A comparison of four different estimation approaches for prognostic survival oral cancer model - Wan Ahmad, Wan Muhamad Amir; Yaqoob, Muhammad Azeem; Mohd Ibrahim, Mohamad Shafiq (DigitalCommons@WayneState, 2020)
Four types of estimation approaches for prognostic survival oral cancer model building are considered via a SAS algorithm: Efron’s Method, Exact Method, Breslow’s Method, and Discrete Method. Each method is illustrated separately and compared according to their coefficient parameter. An approach is considered by adding a bootstrapping technique for each handling ties method and a complete SAS algorithm is supplied for each proposed method, including methods for handling ties.